Performance, interatividade e localidade em “Santos Football Music” de Gilberto Mendes - Fernando de Oliveira Magre; Luciana Fernandes Rosa (Revista Vortex, 2021)
This work presents an analysis of Gilberto Mendes’ “Santos Football Music” performed by the Orquestra Sinfônica de Santos in 2005 and recorded on video as part of the documentary “A Odisseia Musical de Gilberto Mendes” (2006). This work is characterized as a practice of music-theater, in which scenic and visual elements are combined with sound elements. The participation of the audience in the performance is also a fundamental component of the work. Deviating from an analytical perspective focused on the object-score, in this article we seek to approach the musical work from the point of view of its performance. To do so, we rely on Thomas Turino's (2008) distinctions in ways of music making and Arjun Appadurai's (1996) locality perspective.